Comparing scientific productivity using Scopus and Web of Science (WoS): a case of Indian R&D laboratories. Issue 3 (2nd September 2021) - Kumar, Abhishek
ABSTRACT: The organisations work on the foundation, i.e. defined vision and mandates or say Goals. These goals keep on reminding about the targets, achievements and performance of institutions. The indicators that are established for performance evaluation are recognised as a yardstick. The performance evaluation of service industries like R&D is very difficult since they have intangible output(s). During performance measurement of CSIR laboratories, indicators like publications and patents are well established but few more indicators like 3Ps (Project, Patents and Publications) were identified which result in enhancing the organisational productivity. This measurement technique is derived with a scope to propose a new and holistic system of measuring performance of R&D, which can enable allocation of resource in a rational mode.